Two cooperative multicast schemes of scalable video in relay‐based cellular networks. Issue 7 (1st May 2015) - Hwang, Duckdong; Chau, Phuc; Shin, Jitae; Lee, Tae‐Jin
Abstract : This study investigates the cooperative multicast of scalable video over dedicated relay‐based cellular networks. Different layers in a scalable video tend to have different transmission quality requirements, and legacy cellular network has limitations in providing homogeneous service quality within its coverage area. The authors propose two realistic cooperative transmission schemes with a capacity performance analysis for scalable video over dedicated relay‐based cellular networks. The proposed transmission schemes with multiple antennas at an evolved node B and the dedicated relay utilise the combinations of beamforming and space‐time coding in order to enhance the multicast performance of scalable video. The proposed schemes ensure that the received base layer (BL) of scalable video guarantees the minimum video quality to all user terminals throughout the cell coverage with given outage probability, while the terminals inside the relay coverage can achieve better video quality by receiving both the BL and additional enhancement layer data according to the received channel condition. The antennas configuration and the video type determine which multicast scheme to choose.